The Competitiveness of Polish Resource-and Labour-Intensive Exports in the Context of Membership of the European Union - Michalski , Bartosz (Studia Oeconomica Posnaniensia, 2018)
The paper focuses on the evolution and evaluation of the technological intensity of Polish exports. A particular emphasis is placed on the resource- and labour-intensive (R+L) product clusters. The analysis is supplemented with a case study covering Polish-German trade in the clothing industry. The issues discussed in the paper relate to the broader context of a discussion about the economic security of Poland, in particular, the threat of sustaining a developmental gap in the form of the middle-income trap. The results of the research revealed that the competitive advantages of most R+L categories in Polish exports, including the most important ones, have deteriorated. It is thus a contribution to the debate on measures aimed at strengthening the economic development of Poland and addressing structural burdens.